18x+-5=3(6x+-2)

Simple and best practice solution for 18x+-5=3(6x+-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x+-5=3(6x+-2) equation:


Simplifying
18x + -5 = 3(6x + -2)

Reorder the terms:
-5 + 18x = 3(6x + -2)

Reorder the terms:
-5 + 18x = 3(-2 + 6x)
-5 + 18x = (-2 * 3 + 6x * 3)
-5 + 18x = (-6 + 18x)

Add '-18x' to each side of the equation.
-5 + 18x + -18x = -6 + 18x + -18x

Combine like terms: 18x + -18x = 0
-5 + 0 = -6 + 18x + -18x
-5 = -6 + 18x + -18x

Combine like terms: 18x + -18x = 0
-5 = -6 + 0
-5 = -6

Solving
-5 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 16=9 | | (7y-1)=(11y+19) | | 2x^3-12x^2+18x=0 | | (x+7)(x-6)=(x+7) | | 7a-3=3-3a | | 33+49= | | 4y-70=12y-2 | | 7x-6(x-1)=8 | | x/-5=-26 | | -2=-5+y | | 58y=29(2y+15) | | x-4=-x+4 | | Y=2x^2-5x+9 | | 5b^2-17b-12=0 | | y+-5=-(5+-y) | | 2(x+1)+40=-4x | | (9x+37)=(6x+8) | | 7/8=m+3/8 | | 3+15p-1=8p+12-3p | | 2z^2+11z+1=7 | | 2S^2-s-15=0 | | bx+a=5a-c | | 2x-x+3=15 | | (4/3x)-(1/3)-x+7 | | 1/8=4^8x-4 | | 3(-4b+2)+4b=-22 | | 12x-10+70=180 | | 14+(-2q+5)=-2q+9 | | 4+z+6=-8-12 | | 4+2+6=-8-12 | | 1-3v+10=0 | | 20x^3-14x^2+2x=0 |

Equations solver categories